2017
DOI: 10.3847/1538-4357/aa6c59
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Solar Coronal Jet with Two Phases

Abstract: Jets often occur repeatedly from almost the same location. In this paper, a complex solar jet was observed with two phases to the west of NOAA AR 11513 on 2012 July 2. If it had been observed at only moderate resolution, the two phases and their points of origin would have been regarded as identical. However, at high resolution we find that the two phases merge into one another and the accompanying footpoint brightenings occur at different locations. The phases originate from different magnetic patches rather … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Sterling et al (2015) mention that a likely trigger of the eruption is magnetic flux cancelation in the feet of the magnetic field in and around the minifilament flux rope, and Panesar et al (2016Panesar et al ( , 2018 have presented compelling evidence that in most coronal jets in quiet regions and coronal holes flux cancelation at the polarity inversion line under the pre--jet minifilament triggers the eruption. The results of Panesar et al (2016Panesar et al ( , 2018 are from 23 randomly selected jets, and are consistent with many recent studies of smaller samples of jets in which there is evidence for flux cancelation being the trigger (e.g., Young & Muglach 2014a, 2014bChen & Innes 2016;Chen et al 2017;Zhu et al 2017;Chandra et al 2017). The present paper is a direct follow--on to the Sterling et al (2015) paper.…”
supporting
confidence: 90%
“…Sterling et al (2015) mention that a likely trigger of the eruption is magnetic flux cancelation in the feet of the magnetic field in and around the minifilament flux rope, and Panesar et al (2016Panesar et al ( , 2018 have presented compelling evidence that in most coronal jets in quiet regions and coronal holes flux cancelation at the polarity inversion line under the pre--jet minifilament triggers the eruption. The results of Panesar et al (2016Panesar et al ( , 2018 are from 23 randomly selected jets, and are consistent with many recent studies of smaller samples of jets in which there is evidence for flux cancelation being the trigger (e.g., Young & Muglach 2014a, 2014bChen & Innes 2016;Chen et al 2017;Zhu et al 2017;Chandra et al 2017). The present paper is a direct follow--on to the Sterling et al (2015) paper.…”
supporting
confidence: 90%
“…Chen et al ( 2017) observed a complex jet with two intrinsic phases to the west of NOAA AR 11 513 on July 2, 2012 with high spatial resolution using data obtained by Atmospheric Imaging Assembly (AIA) (Lemen et al, 2012) on-board the Solar Dynamics Observatory (SDO) and analyzed the driving mechanism of the jet. In this paper, we report the observation of multiple blobs and analyze the evolution of the detected blobs in the complex jet which were studied by Chen et al (2017). We also investigate the physical properties of these jets and present possible mechanisms responsible for the evolution of the jet.…”
Section: Introductionmentioning
confidence: 99%
“…A series of jets appeared at the west edge of AR 11 513 on 2012 July 2 (Chen et al, 2015). One of these jets occurred at around 22: 30 UT, and the driving mechanism are studied by Chen et al (2017). The complex jet went through two phases originating from different magnetic patches.…”
Section: Introduction Of a Jetmentioning
confidence: 99%
See 1 more Smart Citation
“…Most theories and observations suggest that the rotational motion of solar coronal jets should be a process involving "untwisting"[e.g., Shibata and Uchida, 1986;Jibben and Canfield, 2004;Moreno-Insertis et al, 2008;Pariat et al, 2009;Liu et al, 2009;Shen et al, 2012;Lee et al, 2015;Fang et al, 2014;Filippov et al, 2015b;Liu et al, 2016b]. The physical scenario of "untwisting" jets is usually described as follows: a newly emerging [e.g., observations in Liu et al, 2016b;Zheng et al, 2018] or a pre-existing closed flux system [disturbed by footpoint motions, e.g., observations in Chen et al, 2017] reconnects with the ambient open magnetic field, during which twists contained in the closed flux system could be passed into the open fields and are then released during the rotational motion of the associated jet. Following this idea, a natural question may be raised: will all the twists stored in the pre-reconnection flux rope be released during the coronal jet eruption?…”
Section: Introductionmentioning
confidence: 99%